Rehabilitation with ear prosthesis linked to osseointegrated implants - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Haddad, Marcela Filie [UNESP]; Moreno, Amalia [UNESP] (Wiley-Blackwell, 2012)
Background: The absence of an ear, which can be the result of a congenital malformation, surgical tumour resection or traumatic injury, is a significant aesthetic problem. Attachment of ear prostheses with adhesives can cause local irritation for the wearer and affect the colour of the prostheses. Use of implants in craniofacial reconstruction can improve the retention and stability of prostheses giving to patient greater comfort and security relative to adhesive attachment.Objective: The aim of this report was to present a clinical case of a mutilated patient who was rehabilitated by means of installing an ear prosthesis fixed through osseointegrated implants.Materials and methods: The patient had two implants installed in the mastoid region that were linked by a bar, and a clip-type system was used. The ear prosthesis was constructed from medical-use silicone, pigmented to match the patient's skin colour and linked to the retention system.Conclusion: The patient's rehabilitation was satisfactory from both a functional and an aesthetic point of view, making it possible for the patient to return to a normal social life and regain lost self-esteem.
Keywords: maxillofacial prosthesis; aesthetic; osseointegration; implant